Penerapan Sistem Akuntansi Berbasis Android Untuk Menyusun Laporan Keuangan Sederhana Usaha Mikro Desa Paluh Manan - Masyitah, Emi; Liswanty, Ina; Lubis, Citra Windy; Lubis, Nurul Izzah; Pohan, Nadil Arzaq; Priyanti, Utari (Publikasi Pengabdian Masyarakat, 2022)
Every business is expected to at the very least know how much it spends on capital, how much it makes in profits, and how much it spends on operating expenditures. As a result, business owners can assess the capability of their organization and make development plans for it based on the data that is recorded. Empowering Medium-Sized, Small-Sized, and Micro-Enterprises (MSMEs) is crucial for the economy. MSME development calls for a comprehensive and ecosystem-wide strategy that addresses at least six factors: policy, market access, human resource capability, assistance, and culture. Combining these six elements and boosting MSME development initiatives even more depends on digitalization. The Paluh Manan Village community of UMKM performers is the service's intended audience. Ten people participated in the dedication function, which was held on November 8, 2022, at Paluh Manan Village. According to the evaluation's findings, this community service project's outcomes and advantages included helping participants learn how to create simple financial reports on Android for use in their day-to-day operations.